Chemoimmunomodulation in triple negative breast cancer: a key to maximizing anti-PD-1 chemoimmunotherapeutic efficacy - Mohammed O. Gbadamosi; Elizabeth Molchan; Mariana S. Makarem; Kennedy L. Coleman; Alyssa C. Ohaegbulam; Kathleen H. Streeks (OncoImmunology, 2025)
Triple-negative breast cancer (TNBC) is among the aggressive subtype of breast cancer with a distinct lack of viable treatment strategies and poor clinical outcomes. Anti-PD-1 chemoimmunotherapy (CIT), which leverages the vast array of immunomodulatory effects induced by chemotherapeutic agents to potentiate anti-PD-1 blockade, has emerged as a promising standard-of-care treatment option. However, the clinical benefit from anti-PD-1 CIT has been limited and heterogeneous in advanced TNBC. One of the major reasons for these limitations is the lack of understanding regarding the immunomodulatory properties of chemotherapeutics with respect to individual patients. In this review, we discuss the immunomodulatory properties of first-line chemotherapeutic agents in TNBC and the potential benefits that optimizing chemoimmunomodulation offers toward maximizing CIT efficacy in TNBC.